RETRACTED: Using music in ESG education - Regnerová Olga; Chelombitko Tetiana; Rakityanska Lyudmyla; Zaplatynska Anna; Sizhuk Inna; Bondar Svitlana; Derbak Olha (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001